First enantioselective synthesis of (2S,3S)-3-hydroxy-L-arginine via proline catalyzed alpha-aminooxylation of aldehyde and Pd-catalyzed ether-directed aza-Claisen rearrangement - Ahuja, Brij Bhushan; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise enantioselective synthesis of (2S,3S)-3-hydroxy-L-arginine with an overall yield of 10.9% and 98% ee, starting from commercially available 1,4-butanediol in ten linear steps has been achieved. The key chiral inducing steps are D-proline catalyzed sequential alpha-aminooxylation/Horner-Wadsworth-Emmons olefination of an aldehyde and the subsequent diastereoselective MOM-ether-directed Pd-catalyzed aza-Claisen rearrangement of allylic trichloroacetimidate. (C) 2015 Elsevier Ltd. All rights reserved.